크리핑 벤트그래스 퍼팅그린에서 동절기 및 그린업 시기 잔디 착색제 활용 - 이상진(Sang-Jin Lee); 장석원(Seog-Won Chang); 김기동(Ki-Dong Kim); 심경록(Kyung-Rok Shim); 이정호(Jeong-Ho Lee) (Weed & turfgrass science, 2020)
우리나라 골프장에서 착색제는 잔디 품질의 시각적 측면에서 동계 잔디의 녹색을 선명하게 하고 녹색유지 기간을 연장하기 위하여 사용된다. 본 연구는 착색제 활용 범위를 확대하고자 국내 골프장에 식재되는 크리핑 벤트그래스의 동계기간 중 착색제의 활용 효과에 대하여 연구하였다. 연구결과 겨울동안 착색제가 처리된 벤트그래스는 착색제의 종류에 상관없이 착색하지 않은 대조구보다 식생지수와 엽록소 함량이 증가하였다. 또한 착색제 처리 기준량의 1/2 배액 보다 기준 배액을 처리할 경우 식생지수와 엽록소 함량이 더 높았다. 잔디착색제의 녹색도 유지기간은 착색제 별로 다르게 나타나 착색제 선정 시 착색능력과 동계 지속력을 고려해서 착색제를 선택해야 할 것으로 판단된다. 뿌리길이와 지상부 밀도 측정 결과 실험에 사용된 잔디착색제는 잔디 생육에 큰 영향을 주지 않았으며, 이듬해 봄에 전체 실험구에서그린업도 정상적으로 진행되었고 잔디 생육도 정상적으로 진행되었다. 결론적으로 잔디의 휴면기간 착색제를 사용할경우 녹색 유지기간을 연장할 수 있고, 이듬해 봄철 그린업에 좋은 영향을 줄 수 있으며, 동절기 퍼팅그린의 시각적 품질을 유지할 수 있어 내장객의 만족도를 높일 수 있는 방안 중 하나가 될 것으로 판단된다. From the visual aspect of turf grass quality, turf colorant has been used to keep the vividness of green color and extend the duration of green color of turfgrass during the winter season of Korean golf courses. This study was conducted to investigate the effects of turf colorant application on creeping bentgrass planted in domestic golf courses during the winter. According to the result of this experiment, the colorant-applied zone, regardless of dilution rate and colorant types, showed higher or similar normalized difference vegetation index (NDVI) and chlorophyll contents than in the control during the winter or the period of greenup. In addition, the NDVI and chlorophyll contents were higher in 1x treatment than 1/2x treatment. Because of the difference of green color duration of the colorants, the selection of turf colorant should consider its properties like coloration rate. According to the evaluation of root length and turf density, the colorant applied in the experiment had little effect on the growth of turfgrass, green-up started at the experiment zone in March, while as turf grass grew normally. In conclusion, the coloration rate and duration should be considered selection of turf colorant. It is possible to extend the green color duration by using the colorant during the winter season and it is confirmed that there is no damage to green-up in the following year. Also, using colorants will be one of the ways to maintain the visual quality until the recovery and increase the satisfaction of the customers. KCI Citation Count: 0